Identificación de especies palinolínicas usadas por la abeja real (melipona mimetica cockerell) en época lluviosa, en el cantón Baba - Los Ríos, Ecuador - García Arana, Jean Carlos (2020)
X. SUMMARY Hymenoptera provide great benefits to man. Bees are important pollinating agents of wild and cultivated plants, the domestic bee is known for the production of honey and wax elements of great utility in Ecuador. In this work, the plant species used by the queen bee (Melipona mimetica) were recorded by direct observation on the estate of Mr. José Isidro Garcia Suarez in the San Antonio de Aguas Blancas compound, Guare parish of Baba canton, Los Ríos Province where the presence of the pecoreando bee was verified, which are described botanically, including the dates of flowering and the determination of the pollen color of each one of them. Finally, the meliponícola calendar for planning future studies and / or topics of interest related to beekeeping in Ecuador is presented, highlighting that it is the first known record of this type for this area.